Characterization and microwave healing properties of different asphalt mixtures suffered freeze-thaw damage. (20th October 2021) - Lou, Baowen; Sha, Aimin; Barbieri, Diego Maria; Liu, Zhuangzhuang; Zhang, Fan; Jiang, Wei; Hoff, Inge
Abstract: Asphalt materials display the inherent ability to heal micro-cracks and the microwave heating technique can help accelerate this process thus promoting the creation of a durable asphalt pavement. The objective of this study is to investigate the difference in healing potential between two representative types of asphalt mixtures, namely dense asphalt concrete (AC-13) and open-graded friction course concrete (OGFC-13), suffered freeze-thaw (F-T) damage. In particular, OGFC concrete is especially susceptible to water damage due to its high percentage of air voids. The effect of gradation and F-T damage on the healing performance of asphalt mixtures is appraised by means of three-point bending test, freeze-thaw splitting test and X-ray computed tomography test. Results demonstrate that the gradation exerts a clear influence on the microwave healing behavior and microwave absorber content. In addition, the mechanical strength of mixtures characterized by F-T damage can be partially restored with microwave heating treatment: the healing efficiency of OGFC asphalt specimen after three cycle F-T cycles is still satisfactory. As probed with X-ray computed tomography, the proportion of micropores increases, while the amount of mesopores and macropores decrease after the microwave treatment. However, thermal heating technics are not suitable for further healing when the structural deformation of the OGFC sample occurs due to the F-T damaging process. The research outcomes can contribute to understand the microwave healing behavior for different asphalt mixture types and characterize the healing mechanism of mixtures suffered F-T damage.